Mavrilimumab, a Fully Human Granulocyte–Macrophage Colony‐Stimulating Factor Receptor α Monoclonal Antibody: Long‐Term Safety and Efficacy in Patients With Rheumatoid Arthritis. Issue 5 (31st March 2018) - Burmester, Gerd R.; McInnes, Iain B.; Kremer, Joel M.; Miranda, Pedro; Vencovský, Jiří; Godwood, Alex; Albulescu, Marius; Michaels, M. Alex; Guo, Xiang; Close, David; Weinblatt, Michael
Abstract : Objective: Mavrilimumab, a human monoclonal antibody, targets granulocyte–macrophage colony‐stimulating factor receptor α. We undertook to determine the long‐term safety and efficacy of mavrilimumab in rheumatoid arthritis patients in 2 phase IIb studies (1071 and 1107) and in 1 open‐label extension study (ClinicalTrials.gov identifier: NCT01712399). Methods: In study 1071, patients with an inadequate response to disease‐modifying antirheumatic drugs (DMARDs) received mavrilimumab (30, 100, or 150 mg) or placebo every other week plus methotrexate. In study 1107, patients with an inadequate response to anti–tumor necrosis factor agents and/or DMARDs received 100 mg mavrilimumab every other week or 50 mg golimumab every 4 weeks plus methotrexate. Patients entering the open‐label extension study received 100 mg mavrilimumab every other week plus methotrexate. Long‐term safety and efficacy of mavrilimumab were assessed. Results: A total of 442 patients received mavrilimumab (14 of 245 patients from study 1071, 9 of 70 patients from study 1107, and 52 of 397 patients from the open‐label extension study discontinued mavrilimumab treatment throughout the studies). The cumulative safety exposure was 899 patient‐years; the median duration of mavrilimumab treatment was 2.5 years (range 0.1–3.3 years). The most common treatment‐emergent adverse events (AEs) were nasopharyngitis (n = 69; 7.68 per 100 patient‐years) and bronchitis (n = 51; 5.68 per 100 patient‐years). At weeks 74 and 104, 3.5% and 6.2% of patients, respectively, demonstrated reduction in forced expiratory volume in 1 second, while 2.9% and 3.4% of patients, respectively, demonstrated reduction in forced vital capacity (>20% reduction from baseline to <80% predicted). Most pulmonary changes were transient and only infrequently associated with AEs. Mavrilimumab at 100 mg every other week demonstrated sustained efficacy; at week 122, 65.0% of patients achieved a Disease Activity Score in 28 joints using the C‐reactive protein level (DAS28‐CRP) of <3.2, and 40.6% of patients achieved a DAS28‐CRP of <2.6. Conclusion: Long‐term treatment with mavrilimumab maintained response and was well‐tolerated with no increased incidence of treatment‐emergent AEs. Safety data were comparable with those from both phase IIb qualifying studies.